Videos of Savi Oriented Learning Model Based on Sparcol Scribe in Class IV Students - Niya Selfiana Panggabean; I Kadek Suartama; I Made Tegeh (Universitas Pendidikan Ganesha, 2021)
The low learning outcomes of fourth-grade elementary school students in social studies learning are caused by less attractive learning packaging. In addition, there is no application of interactive learning videos in the classroom. The research objective is to develop interactive learning videos. This type of research is the development of the ADDIE model. Data collection methods consist of interviews, observation, document recording, and distributing questionnaires. This study consisted of 3 experts, 6 small group students, and 3 individual test students. The instrument used to collect data is a questionnaire. The technique used to analyze the data is descriptive qualitative and quantitative analysis. The study results are the results of a review by content experts in the field of study with excellent qualifications (96.66%). The results of the review of media design experts with excellent qualifications (96%). The results of the review of media experts with excellent qualifications (90%). The results of individual trials with excellent qualifications (96.67%). The results of the small group trial with excellent qualifications (95.55%). It can be concluded that the use of interactive learning videos is feasible to be applied in learning. Learning videos can increase students' interest in social science.